The Emerging Roles of the Calcineurin-Nuclear Factor of Activated T-Lymphocytes Pathway in Nervous System Functions and Diseases - Maulilio John Kipanyula; Wahabu Hamisi Kimaro; Paul F. Seke Etet (Journal of Aging Research)
The ongoing epidemics of metabolic diseases and increase in the older population have increased the incidences of neurodegenerative diseases. Evidence from murine and cell line models has implicated calcineurin-nuclear factor of activated T-lymphocytes (NFAT) signaling pathway, a Ca2+/calmodulin-dependent major proinflammatory pathway, in the pathogenesis of these diseases. Neurotoxins such as amyloid-β, tau protein, and α-synuclein trigger abnormal calcineurin/NFAT signaling activities. Additionally increased activities of endogenous regulators of calcineurin like plasma membrane Ca2+-ATPase (PMCA) and regulator of calcineurin 1 (RCAN1) also cause neuronal and glial loss and related functional alterations, in neurodegenerative diseases, psychotic disorders, epilepsy, and traumatic brain and spinal cord injuries. Treatment with calcineurin/NFAT inhibitors induces some degree of neuroprotection and decreased reactive gliosis in the central and peripheral nervous system. In this paper, we summarize and discuss the current understanding of the roles of calcineurin/NFAT signaling in physiology and pathologies of the adult and developing nervous system, with an emphasis on recent reports and cutting-edge findings. Calcineurin/NFAT signaling is known for its critical roles in the developing and adult nervous system. Its role in physiological and pathological processes is still controversial. However, available data suggest that its beneficial and detrimental effects are context-dependent. In view of recent reports calcineurin/NFAT signaling is likely to serve as a potential therapeutic target for neurodegenerative diseases and conditions. This review further highlights the need to characterize better all factors determining the outcome of calcineurin/NFAT signaling in diseases and the downstream targets mediating the beneficial and detrimental effects.